2020
DOI: 10.1103/physreva.102.013511
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Ramsey methods in the spectroscopy of coherent-population-trapping resonances

Abstract: We present a rigorous justification for the applicability of the recently developed methods of generalized autobalanced Ramsey spectroscopy (GABRS) [V. I. Yudin et al., Phys. Rev. Appl. 9, 054034 (2018)] and combined error signal in Ramsey spectroscopy (CESRS) [V. I. Yudin et al., New J. Phys. 20, 123016 (2018)] for resonances of coherent population trapping (CPT). A protocol of modified combined error signal for CPT resonances is also proposed, in which two successive interrogations of atoms under different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Nevertheless, Ramsey-CPT spectroscopy suffers from a residual sensitivity to light-shifts, experienced by the atoms during the light pulses. Advanced Ramsey-based tailored interrogation protocols, based on two consecutive Ramsey sequences with different dark times, have then been proposed and demonstrated in various types of atomic clocks for enhanced light-shift mitigation [20][21][22][23][24][25][26] . In standard vapor cell clocks, it was demonstrated that the symmetry of the interrogation was of crucial importance to tackle an atomic memory effect, mainly linked to the limited duty cycle of the probing sequence, and then to optimize light-shift mitigation 11,22 .…”
mentioning
confidence: 99%
“…Nevertheless, Ramsey-CPT spectroscopy suffers from a residual sensitivity to light-shifts, experienced by the atoms during the light pulses. Advanced Ramsey-based tailored interrogation protocols, based on two consecutive Ramsey sequences with different dark times, have then been proposed and demonstrated in various types of atomic clocks for enhanced light-shift mitigation [20][21][22][23][24][25][26] . In standard vapor cell clocks, it was demonstrated that the symmetry of the interrogation was of crucial importance to tackle an atomic memory effect, mainly linked to the limited duty cycle of the probing sequence, and then to optimize light-shift mitigation 11,22 .…”
mentioning
confidence: 99%